EKSPLORASI ETNOMATEMATIKA PADA BATIK SOEDIRMAN DI PURBALINGGA - Deka, Silvia; Anggun Badu (Satya Widya, 2024)
Ethnomathematics is the study of mathematics that examines the correlation between mathematics and cultural activities within a particular community. Ethnomathematics refers to an activity in society that is carried out in daily activities as a culture related to mathematics.  This culture is found in cultural heritage related to General Soedirman, one of which is Batik Soedirman. Soedirman Batik is a new innovation in batik craftsmanship found in Purbalingga Regency. This research aims to explore the mathematical elements in Soedirman Batik motifs. The researcher employed qualitative research methods with an ethnographic approach. The subjects of this study included the Regional National Crafts Council of Purbalingga, Wastralingga Batik Center, the owner of Tien Batik Center, and batik artisans. Data collection techniques involved interviews, observations, and documentation. Data analysis was conducted using Spradley's model, which includes domain analysis, taxonomic analysis, componential analysis, and thematic analysis. The results of this study indicate the presence of mathematical elements such as repeating patterns, unit conversion, plane figures, lines, congruence, geometric transformations, and trigonometric function graphs in the Soedirman Batik motifs.